Infections during extracorporeal membrane oxygenation: epidemiology, risk factors, pathogenesis and prevention - Biffi, Stefano; Di Bella, Stefano; Scaravilli, Vittorio; Peri, Anna Maria; Grasselli, Giacomo; Alagna, Laura; Pesenti, Antonio; Gori, Andrea (International journal of antimicrobial agents, 2017)
•ECMO patients have a higher infectious risk than other critically ill patients.•Infections during the ECMO run significantly affect mortality rates.•Colonisation of ECMO cannulae and oxygenator could have a role in causing bloodstream infections.•Enterobacteriaceae are the most frequent agents of ventilator-associated pneumonia in this setting.•There are no data supporting an antibiotic prophylaxis strategy during ECMO. Extracorporeal membrane oxygenation (ECMO) is a life support technique used in patients with respiratory and/or cardiac failure. The ECMO circuit consists of vascular cannulae, a pump and an artificial lung. Infections are among the most common complications associated with ECMO and have a significant impact on the mortality rate. Here we present a narrative literature review regarding the epidemiology, risk factors, pathogenesis and prevention of infectious complications during ECMO support. The prevalence of hospital-acquired infections during ECMO is 10–12% and their occurrence is likely to be more frequent compared with other critically ill patients. Coagulase-negative staphylococci, Candida spp., Enterobacteriaceae and Pseudomonas aeruginosa are the most frequently involved pathogens. A high incidence of ventilator-associated pneumonia was reported (24.4 cases/1000 ECMO days), with a major role unexpectedly played by Enterobacteriaceae. The infectious risk was shown to increase along the duration of the ECMO run, which represents the most important risk factor for the development of infections. Other ECMO-specific factors predisposing to infections include the severity of illness in ECMO patients, the high risk of bacterial translocation from the gut, and ECMO-related impairment of the immune system. Another important issue could be microbial colonisation of catheters, ECMO cannulae and the oxygenator, which is consistent with most commonly observed aetiologies.